PENGARUH UKURAN BUTIR SERBUK FLY ASH TERHADAP KEKUATAN IMPACT BAHAN KOMPOSIT BERMATRIKS EPOXY - Setiawan, Agus; Savetlana, Shirley; Ibrahim, Gusri Akhyar (FT UNILA, 2013)
Mixing types of epoxy polymers with fly ash (fly ash) coal into composite materials is expected to be one of the ways to look for an alternative to metal materials. Mixing two different materials is intended to improve the mechanical properties of composites by utilizing waste coal as a reinforcing material. Making specimens was based on differences in particle size of the fly ash powder. Fly ash sifted with a sieve to obtain a variation of the size of the fly ash particles with a size of 40 mesh, 80 mesh and 120 mesh. While the epoxy resin used was a general purpose type (Bisphenol Aepichlorohydrin) Bakelite EPR 174 with a ratio between the epoxy resin and hardener 1:1. After getting the fly ash according to the desired size, made by mixing epoxy resin through the calculation of the mass fraction. The process of mixing epoxy resin with coal fly ash waste is done with matrix mixing ratio by 60% and 40% fly ash. Then do the impact test for pure epoxy resin and for composites. Fracture area photo by scanning electron microscope (SEM) was used to analyze the causes of failure in composites. Testing was conducted ann accordance with the standard impact test ASTM D 6110. The test results showed the addition of fly ash particles with increasing particle size of 40 mesh, 80 mesh and 120 mesh can improve the impact strength of the composite. Highest impact strength of the composite obtained at 120 mesh particle size of 3.967 x 10-3 J/mm2. With the decrease in the size of particles, extensive contact between the surface of fly ash with resin will be many more. So, to the improve impact strength. In the SEM image results look excellent interface bonding between the matrix with fly ash particles. In the composite looks much voids or porosity.Keywords: epoxy, composites, fly ash, impact test, SEM photos, the mechanical properties.